Efficiency in intrahousehold resource allocation - Fafchamps, Marcel (International Food Policy Research Institute, 1998)
This paper examines the allocation of productive resources within rural households of poor countries. Building upon the existing literature, it provides a consistent framework from which to study productive efficiency and intrahousehold equity. The topics discussed include returns to scale and household centralization; specialization and gender casting; separate spheres and commitment failure; labor market cartelization and discrimination; and the provision of home public goods in the presence of free riding. We show that intrahousehold productive inefficiency should not arise unless household members are prevented from entering into enforceable side contracts. Our analysis predicts that intrahousehold inefficiency increases with factors that exacerbate commitment failure such as short time horizon, low assets, unequal stakes in the household, and poor external enforcement. Patrimonial laws and customs regarding inheritance and divorce can be understood as efforts to mitigate commitment failure within the household.